DIFFERENT METHODS OF MODELING IN PRIMARY CLASSES - Alijon Asimov; Abduvaliyeva Muslimaxon Shavkatjon qizi (Zeta Repository, 2023)
The article analyzes the use of models in the process of teaching students in mathematics lessons. The use of models in solving complex problems develops imaginative thinking of students, contributes to the development of abstract thinking, the development of various forms of mental activity, and maintaining interest in the subject.